Extended myectomy in the treatment of patients with hypertrophic obstructive cardiomyopathy - Kuć, Mateusz; Kołsut, Piotr; Różański, Jacek; Dąbrowski, Maciej; Kłopotowski, Mariusz; Kumor, Magda; Kowalski, Mirosław; Kopyłowska, Natalia; Kuriata, Jarosław; Kuśmierczyk, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Partial resection of the septal muscle is a well-established and effective method of surgical treatment for patients with hypertrophic obstructive cardiomyopathy (HOCM). The procedure is characterized by a low operative mortality rate and long-term clinical improvement that has been confirmed in numerous publications. Mitral insufficiency in patients with HOCM is mostly functional due to the effect of systolic anterior motion (SAM). Aim: To present the early results of surgical treatment provided to HOCM patients and to compare the effectiveness of two surgical procedures: isolated myectomy and myectomy combined with mitral valve replacement. Material and methods: The study analyzed a group of 49 patients (20 women) with HOCM who underwent surgical treatment between 2012 and 2015. Isolated myectomy was performed in 67.25% (n = 33) of patients, myectomy combined with mitral valve replacement in 30.61% (n = 15), and 1 (2.04%) patient underwent myectomy combined with mitral valvuloplasty (papillary muscle repositioning). Results: A greater reduction of the left ventricular outflow tract (LVOT) gradient was observed in the population with concomitant mitral valve replacement in comparison to patients after isolated myectomy; the difference was statistically significant (p = 0.020). No significant correlation was observed between residual SAM and the grade of mitral regurgitation (p = 0.699) or between residual SAM and the LVOT gradient (p = 0.280). Conclusions: Surgical myectomy is a well-established, effective method of reducing increased LVOT gradients in patients with HOCM. Additional mitral valve replacement may be associated with greater reductions of the LVOT gradient in the early postoperative period. Valve replacement should be considered in patients with concomitant mitral valve degeneration and patients with narrowed left ventricular cavities.